Analisis Indikasi dan Pola Kemiskinan Masyarakat Di Kota Makassar Provinsi Sulawesi Selatan - Rasyid, Rusman; Dirawan, Gufran D; Umar, Ramli; Pertiwi, Nurlita (UNM Environmental Journals, 2017)
Makassar city as the capital of South Sulawesi, can not be spared from the phenomenon ofpoverty. The development of Makassar relatively rapidly the last few years have led to thiscity was the destination of migration from other cities in eastern Indonesia that has a levelof development and high population density. This has implications for the increase in thenumber of poor people in this city. Sekaitan with it, this paper aims to present an analysisof the patterns of poverty in Makassar conducted descriptive based on informationgathered through observations, interviews with informants in 100 poor households assamples taken proportionally. The results of these studies show that the poor in Makassartend to fall into the pattern of subsistence poverty, poverty, poverty of protection andunderstanding, but not forming patterns of participation poverty, poverty or lack ofliberties identity. The results of this paper are expected to identify the characteristics of thetypology and determine patterns of urban poor groups that are highly relevant to anattempt by the government to tackle the problem of poverty.